Assessment effect of breast milk on diaper dermatitis - Bahar Seifi; Sheida Jalali; Mohammad Heidari (PAGEPress Publications, 2017)
Diaper dermatitis is the most common dermatological disease of infancy, which occurs and caused by the combined effect of irritants such as diaper, urine and faces. In this study, we intend to evaluate the effect of breast milk on the healing of diaper dermatitis. This study was a clinical trial of 30 infants between 0-12 months of age that were suffering from diaper dermatitis and referred to the Health Centers in Tehran, Iran. The subjects were selected by open study. Infants were divided into two matched groups: case and control. Datagathering tools were the questionnaire that contained two parts: the demographic characteristics of infants and the status of care and condition of the lesion. Data analysis was performed using SPSS/18 software and Mann-Whitney and Chi-Square tests were used. The findings revealed a significant difference between the case and control groups in the number and lesion score of the rashes at the first and third day (P=0.013, P=0.005), these differences were more significant at the fifth day (P=0.004, P=0.001). Because of positive effects of breast milk on healing of diaper dermatitis, it is proposed that educational programs in health centers should be considered by health officials, and the managers would play a key role in increasing knowledge behavior changes in mothers.